Emotional reaction to diagnosis of infertility in Kuwait and successful clients' perception of nurses' role during treatment - Omu Alexander E; Omu Florence E (BMC, 2010)
Abstract Background The unfulfilled desire of millions of infertile couples worldwide to have their own biological children results in emotional distress. This study evaluated the emotional reactions of couples attending a combined infertility clinic in Kuwait and successful clients' perception of nurses. Methods Quantitative and qualitative methods were used. The first phase was by structured interview using two standardized psychological scales: the 25-item Hopkins Symptom Checklist and Modified Fertility Adjustment Scale. Data were collected from 268 couples attending the combined infertility clinic, between October 2002 and September 2007. The second phase was a semi-structured interview of 10 clients who got pregnant following treatment. The interview explored their feelings and perception of the nurses' role. Interviews were transcribed verbatim and analyzed. Results The average duration of infertility was 4 years; 65.7% of the women and 76.1% of men suffered from primary infertility. Emotional reactions experienced were: anxiety in women (12.7%) and men (6%), depression in women (5.2%) and men (14.9%) and reduced libido in women (6.7%) and men (29.9%). Also in men, 14.9% experienced premature ejaculation, 5.2% weak ejaculation and 7.9% had impotence although 4.9% were transient. In the semi-structured interviews, the emotions expressed were similar and in addition to anger, feelings of devastation, powerlessness, sense of failure and frustration. In the survey, 12.7% of the men were found to show more anxiety than women (6%). Although all the 10 women interviewed confirmed they were anxious; only 4 of their partners were reported to be sad or anxious. Successful clients' perception of nurses' roles included nurses carrying out basic nursing procedures, communicating, educating about investigative and treatment procedures, providing emotional support by listening, encouraging, reassuring and being empathetic. Conclusions This study illuminates the emotional reactions of infertile clients. Fertility nurses in Kuwait can provide emotional support through communication. The need for additional and continuous training for nurses employed in fertility settings in Kuwait is paramount.